Mitteilungen der Magnus-Hirschfeld-Gesellschaft. (Berlin : Magnus-Hirschfeld-Gesellschaft, 1984)
Fonds Suzan Daniel (FSD)
Periodiciteit : halfjaarlijks/onregelmatigRedactie : Chodowieckistrasse 41, 10405 Berlin
Duits
Periodiek